Drivers of Land Embodied in International Trade of Rice: The Italian Case Study - Caro, Dario; Sporchia, Fabio (European Journal of Sustainable Development, 2019)
In the last years, a significant increase of imports of Rice from Cambodia and Myanmar into the European Union has been recorded. In particular, Italian farmers were badly affected by the imports of rice from these two Asiatic countries. Indeed, the European Commission in 2019 has therefore decided to re-introduce specific import duties. In turn, such exported rice corresponds to large quantities of land that are driven by consumption of Asiatic rice in Italy. In this study, we estimate the Virtual Land Trade associated with rice trade between Cambodia and Myanmar to Italy. Our analysis combines physical import data and associated land information. The analysis shows the pro-and-con of these debated trade connections also revealing the effect of replacing the Asiatic import demand with domestic production of rice in Italy in terms of land use. The study is relevant in understanding whether patterns of rice consumption, production and trade represent an efficient, and logical, allocation of natural resources. Keywords: Virtual land trade; food; consumer awareness; land footprint; agricultural impact; rice; international trade